Perbaikan dan Pembangunan Jalur Sanitasi Pembuangan MCK di Desa Takofi Kecamatan Moti - Muhammad Muzni Herbelubun; Ahmad Seng; Rudi Hartono; Sandi Rais (Patria Artha Journal of Community (PKM), 2022)
One of the implementations of PKM in 2021 carried out by the Mechanical Engineering study program is the manufacture of MCK, but the construction of MCK sanitation facilities to meet community needs has not been carried out due to the implementation limitations of the PKM program. Sanitation is one of the supporting programs in making MCK. The limited facilities and the behavior of people who use open spaces for defecating, bathing, and others will have an impact on aspects of public health. In this activity, a sanitation distribution from the existing MCK was built; hence water drainage and sewage of The  MCK are not polluted and will be maintained in terms of health. The problems of partners/communities in Takofi village are as follows; disposal of polluted MCK sanitation channels, lack of information about the importance of clean sanitation lines and supporting health aspects, and inadequate MCK sanitation sewer lines. Lack of knowledge of making MCK sanitation lines. The implementation of community service activities, repairing and building sanitation lanes for toilet disposal in Takofi village, Moti sub-district, was carried out for one day. Where the initial stage, the toilets were cleaned, which looked very dirty and were not functioning correctly. After cleaning, the next step is measuring and installing new installation pipes where the old network is no longer working correctly. This pipe installation is also related to another PKM program, namely repairing water wells as a water source to operate this MCK. Several students who participated in the PKM program also carried out this activity.Keywors; Sanitation, MCK, Desa Takofi